Optimization of centrifugal pumps operation for least cost and maximum availability - Abdulnabi, Issa Omran N. (Cranfield University, 2008)
There are five M.O.L. Centrifugal pumps “Main Oil Line” in Ghani oil field for transporting crude oil from Ghani oil field to Joffra oil field at a distance of about 81.25 miles (130Km) then from Joffra oil field to Ras Lanuf Terminal at a distance of about 84.40 miles (135Km). The five centrifugal pumps do not all have the same specifications. Three of these pumps have the same power (255 Kw) and are working with five impellers but the other two pumps have the same power (150 Kw) and are working with six impellers. The efficiency and the head are the same for each pump. So the total power in the pumping system is (1,065 Kw). Usually two out of five centrifugal pumps are operational the other three pumps are on standby in case of failure of one or more pumps. These pumps are 24 years old and subjected to routine maintenance. This project presents a study to optimize the existing pumping system in order to make the capital cost less. The main change will be in pumping station design mainly to decrease the number of the existing centrifugal pumps with less cost and to meet Veba Oil Operations (VOO) requirements. As mentioned, the system is required to transport 45,000 BPD (298 m3/h), during the expected life of the project, which is through the pumping system from Ghani oil field to Joffra oil field then to Ras Lanuf Terminal. This study offers different pump design to evaluate and select the optimum design according to the lowest cost, highest reliability and availability.